2016
DOI: 10.2463/mrms.2014-0141
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Mean Axon Diameter and Intra-axonal Space Volume Fraction of the Human Corpus Callosum: Diffusion q-space Imaging with Low q-values

Abstract: Purpose: Q-space imaging (QSI) is a diffusion-weighted imaging (DWI) technique that enables investigation of tissue microstructure. However, for sufficient displacement resolution to measure the microstructure, QSI requires high q-values that are usually difficult to achieve with a clinical scanner. The recently introduced "low q-value method" fits the echo attenuation to only low q-values to extract the root mean square displacement. We investigated the clinical feasibility of the low q-value method for estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…When this is not the case, CSD and derived AFD metrics can become sensitive to extra-axonal changes. Nevertheless, the AFD profile we observed across the CC is largely consistent with histological (Aboitiz et al, 1992) and low q-value imaging data (Suzuki et al, 2016) describing axon diameter and density. This increases confidence in the observed differences being, at least in part, due to genuine microstructural differences affecting the number, size and/or density of callosal axons.…”
Section: The Relationship Between Different Diffusion Measures and Microstructuresupporting
confidence: 87%
“…When this is not the case, CSD and derived AFD metrics can become sensitive to extra-axonal changes. Nevertheless, the AFD profile we observed across the CC is largely consistent with histological (Aboitiz et al, 1992) and low q-value imaging data (Suzuki et al, 2016) describing axon diameter and density. This increases confidence in the observed differences being, at least in part, due to genuine microstructural differences affecting the number, size and/or density of callosal axons.…”
Section: The Relationship Between Different Diffusion Measures and Microstructuresupporting
confidence: 87%
“…For example, the Aboitiz et al 18 histological examination of 20 post-mortem healthy adult brains showed that the density of small and large diameter axons differs across the anterior-posterior axis of the corpus callosum. This now well-established density pattern has been replicated with other measures in more recent work 19, 20, 21 , including the study by Genc and colleagues 22 that serves as a model of the present investigation. As we noted earlier, it would be important for a number of reasons to establish in vivo metrics that are sensitive to differences in axonal density.…”
Section: Introductionsupporting
confidence: 72%
“…Thus, the primary aim of this study is to address whether RDI is a candidate metric for measuring axonal density in vivo, and further whether it does so better than other available diffusion metrics. To do this, we measured segments of the corpus callosum, which have been known to differ in axonal density on the anterior-posterior axis 18, 19, 23, 24 . We used both a healthy adult sample (n = 840) and a healthy developing sample (n = 129) to test whether previous histological results match the segmental pattern reflected using RDI in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…It is postulated that the cardinal MR abnormality of MERS is a result of transient edema of the myelin sheaths. Because the axons in splenium CC are so tightly packed and have high density, the intramyelinic edema is most readily detected as diffusion restriction in the splenium CC (10). We speculate that these two apparently distinct brain structures of Probst bundles and CC might produce similar MR signal abnormalities under the same pathophysiological conditions, thus causing acute encephalopathy and intramyelinic edema.…”
Section: Figure 3 Diffusion Tensor Imaging (Dti) Showing the Bilatermentioning
confidence: 90%